Halal Knowledge Sharing Intention Among Muslim Students in Tasikmalaya: The Role of Religiosity, Altruism, and Self-Efficacy - Friantoro, Dian; Wahyu Ramadhan, Rifky; Alisa, Juniar (IQTISHADIA, 2025)
Halal knowledge is crucial for Muslims to ensure Sharia-compliant consumption. Muslim university students play a strategic role in spreading halal information, yet their knowledge-sharing culture remains low. This study examines the factors influencing students’ intention to share halal knowledge by integrating spiritual values (religiosity and altruism) with psychological constructs (attitude, subjective norm, and self-efficacy). Using a quantitative approach, data were collected from 548 Muslim university students in Tasikmalaya through purposive sampling. The model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that religiosity, altruism, attitude, subjective norm, self-efficacy, and perceived behavioral control significantly influence the intention to share halal knowledge, with attitude and self-efficacy emerging as the strongest predictors. Moreover, altruism and attitude act as mediators, strengthening the indirect effects of religiosity and self-efficacy on knowledge sharing intention. These findings highlight the importance of integrating spiritual values and psychological constructs to foster a stronger culture of halal knowledge sharing among Muslim students.